THE INFLUENCE OF ENTREPRENEURSHIP SPIRIT ON LABOR COMPETENCE ON PERFORMANCE (CASE STUDY ON THE UMKM COMMUNITY ASSISTED BY WEST JAVA CHAMBER OF COMMERCE) - R Susanto Hendiarto; Silvi Indri Pratiwi (Jurnal Ekonomi, 2023)
The current problem is that the performance of the West Java Kadin-assisted MSME community is still far from expectations, allegedly due to the competence of the workforce which was expected to be a stimulus to produce performance, now has not shown encouraging things, that is also suspected because the spirit of entrepreneurship has not been evenly distributed. The aim of this research is to know the influence of the entrepreneurial spirit workforce competence along with its implications for performance, cases studies to the West Java Kadin assisted MSME community in Bandung. There is also a method that is carried out, namely with a descriptive analysis survey, and the examples used are 48 of the respondents. The variables found came from the respondents, namely their entrepreneurial spirit, workforce competence, and performance. Variation of information collected in the form of primary information. This research yielded results showing that the spirit of entrepreneurship has no effect on workforce competence, the competence of the workforce affects its performance. The spirit of entrepreneurship hos no effect on performance. The implication is that the spirit of entrepreneurship must be continuously inflamed throughout the UMKM community assisted by the West Java Kadin. The object of this research is an example of a response that is used in a limited way for the UMKM community under the Kadin Jabar Bandung, so that further research is needed on the basis of taking various samples and a long time to get better results.